2016
DOI: 10.1177/0886260516641280
|View full text |Cite
|
Sign up to set email alerts
|

Providing and Receiving Sexual Assault Disclosures: Findings From a Sexually Diverse Sample of Young Adults

Abstract: This study utilized a sample of primarily lesbian, gay, bisexual, and queer (LGBQ)-identified young adults from across the United States to pilot test a new instrument, the Reactions Provided to Disclosures Questionnaire (RPDQ), and assess the disclosure experience for both those who provide and those who receive disclosures of sexual assault. Results indicate that the experience of sexual assault disclosure in the LGBQ community is similar to the heterosexual community in that most victims disclose their assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…This limits the generalizability of the study’s findings regarding survivors with other characteristics. Accordingly, future research should examine how the intersections of various demographic factors (such as socioeconomic status, race, and sexual orientation) affect the public self-disclosure experience (Koon-Magnin & Schulze, 2019). In the Israeli context, specifically, particular attention should be given to the plight of Arab and religious survivors, in light of their unique cultural characteristics, which may deter them from disclosures of any kind (Tener et al, 2018; Zeira, Astor, & Benbenishty, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This limits the generalizability of the study’s findings regarding survivors with other characteristics. Accordingly, future research should examine how the intersections of various demographic factors (such as socioeconomic status, race, and sexual orientation) affect the public self-disclosure experience (Koon-Magnin & Schulze, 2019). In the Israeli context, specifically, particular attention should be given to the plight of Arab and religious survivors, in light of their unique cultural characteristics, which may deter them from disclosures of any kind (Tener et al, 2018; Zeira, Astor, & Benbenishty, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Disclosing to formal support providers or informal sources only did not influence receipt of positive social reactions, except for tangible aid, which was more commonly provided by formal support sources. Koon-Magnin and Schulze (2019) found that most victims told a friend about sexual assault and were most likely to receive emotional support social reactions than those telling other support sources. Victims disclosing to formal sources, such as police, medical, or religious personnel, were also more likely to be blamed than those not telling those sources.…”
Section: Resultsmentioning
confidence: 95%
“…Perceived life threat during sexual assault was unrelated to receiving positive social reactions (Ullman et al, 2007) but related to more negative social reactions in sexual assault victims. In a sample of primarily lesbian, gay, bisexual, and queer-identified young adults, experiencing an anal assault was related to receiving more victim-blaming reactions (Koon-Magnin & Schulze, 2019). Sullivan et al’s (2010) study of current victims of IPV showed that sexual IPV victimization was related to receiving both positive and negative social reactions.…”
Section: Resultsmentioning
confidence: 99%
“…That mandatory sexual assault prevention training for faculty was also significantly correlated to reported rapes suggests their vital role in the reporting process. Research has shown that students, both heterosexual and nonheterosexual, are more likely to disclose an assault to a friend rather than law enforcement (Koon‐Magnin & Schulze, 2016). Our analysis had initially included whether or not training was mandatory for students but, given that it was not significantly related to reported rapes, the variable was omitted.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%